Efektifitas Model Think Talk Write (TTW) Pada Keterampilan Menulis Pantun Peserta Didik Kelas IV SD Katolik Gugus I Sembur Paus Lamalera - Henakin, Stefanus Tebajak; Laba, Melkior (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
The formulation of the problem of this study is whether there is a difference in the skills of writing pantun in grade IV students of Catholic Elementary School Gugus 1 Sembur Paus Lamalera by applying the Think Talk Write model? The objectives to be achieved in this study are to test whether there is a difference in the skills of writing pantun in grade IV students of Elementary School Gugus 1 Sembur Paus Lamalera by applying the Think Talk Write model. The type of research in this study is experimental research chosen if the study wants to answer a problem by providing empirical evidence. The data collection technique used in this study is a test. The results of the study showed that the average score of the results of the pantun writing test taught using the TTW model was 95.36; based on the established categorization criteria, the average score of the Indonesian language learning outcomes was categorized as very high. And the average result of the pantun writing test using the conventional model was 76.07, based on the categorization criteria used, the average score of the Indonesian language learning outcomes was in the high category. This shows that the results of the test of writing pantun of students who are taught using the TTW model are different from the results of writing pantun of students who are taught using the conventional model.